Effects of Dispersal for a Logistic Growth Population in Random Environments - Xiaoling Zou; Dejun Fan; Ke Wang (Abstract and Applied Analysis)
We study a stochastic logistic model with diffusion between two patches in this paper. Using the definition of stationary distribution, we discuss the effect of dispersal in detail. If the species are able to have nontrivial stationary distributions when the patches are isolated, then they continue to do so for small diffusion rates. In addition, we use some examples and numerical experiments to reflect that diffusions are capable of both stabilizing and destabilizing a given ecosystem.